Preparation Isotactic Polyropylene Hydrophobic Microporous Flat Sheet via Tips for Membrane Contactor - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman (2014)
The membrane technologies nowadays present the membrane to be applied in most gas separation process. Commonly designed for separating CO from flue gas, membrane contactor ( MC ) is not only able to provide significant advantages required by industries, but also available in Malaysia. Somehow, the membrane technology in Malaysia has many limitations when most of the manufacturers only focus on the application of membrane but not the exploration on membrane fabrication and no production of hydrophobic membrane can be applied in the field of membrane absorption due to high cost, fabrication difficulty and do not meet certain specification required to be applied in specific use in Malaysia. Therefore in this study, the productions of hydrophobic microporous flat sheets were accomplished by using isotactic Polypropylene ( iPP ) and two type diluents: dipentyl ether and methyl salicylate. The measurement of hyrdophobility of membranes produced was conducted by Contact Angle Instrument. Membranes produced by using TIPS were characterized by SEM and FTIR. All membranes show spherical pores, indicating that membranes were formed via liquid-liquid TIPS and strong bond that formed in the membrane show that the membrane produces is stable and high in strength.